Nursing leadership in clinical practice, its efficacy and repercussion on nursing‐sensitive outcomes: A cross‐sectional multicentre protocol study. (2nd August 2022) - Fiorini, Jacopo; Zaghini, Francesco; Mannocci, Alice; Sili, Alessandro
Abstract: Aim: The aim of this study to describe a research protocol for evaluating the relationship between nursing leadership, organisational well‐being and nurse and patient outcomes. Background: The head nurses' leadership style influences the organisational context. When an organisation promotes nurses' well‐being, they perform better performances and are more satisfied and engaged with their job. This reduces stress levels, burnout and absenteeism and improves physical and psychological health. Methods: A multicentre study will be conducted. A self‐report questionnaire will be administered to head nurses and nurses they coordinate. Study findings will include nurse‐sensitive outcomes (e.g., pressure injuries, infections and mortality). Descriptive and correlational analyses will be conducted, and a structural equation model will be tested. Results: Results might verify that a correctly judged leadership style of the head nurse will enhance the organisational context experienced by nurses and improve nursing sensitive outcomes. Conclusion: This study will demonstrate the organisational role of middle managers and the direct repercussions on their staff and patients, understanding the relationship between organisational, process and outcomes variables. Implications for Nursing Management: If the results confirmed the hypothesis, health care managers would cultivate and stimulate the head nurses' leadership style, thus increasing nurses' organisational well‐being and achieving better patient outcomes. No Patient or Public Contribution.